ESTIMASI POPULASI DAN KARAKTERISTIK HABITAT LUTUNG JAWA(Trachypithecus auratus E. Geoffroy Saint-Hilaire, 1812) DI RESORT BANDEALIT TAMAN NASIONAL MERU BETIRI - Rusdi, Muhammad; Muttaqin, Tatag; Aryanti, Nirmala Ayu (Journal of Forest Science Avicennia, 2018)
Changes in forest areas into agricultural areas and settlements cause the loss of some natural habitats, thus threatening the sustainability of the Javanese Lutung population. One of the Javanese Lutung habitats, Meru Betiri National Park. The purpose of this study was to determine the estimated population of Javanese Lutung and Javanese Lutung habitat characteristics in the Bandealit Resort of Meru Betiri National Park. Habitat characteristics were obtained through analysis of vegetation data, environmental data, and data on feed types by calculating the Important Value Index (INP) and its relation to environmental conditions in each habitat type. Population differences and habitat characteristics in each habitat type are obtained through Analysis of Variance (Anova) using SPSS (Statictical Program for Social Science) software. The results showed that the estimated population of Javanese Lutung in Meru Betiri National Park was 104 individuals found in 11 groups in all habitat types where each group consisted of 6-18 individuals. Components that have a real influence on each habitat type are temperature and humidity.